2006
DOI: 10.1590/s0004-27302006000100017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da recuperação do eixo hipotalâmico-hipofisário-adrenal após corticoterapia por meio do cortisol basal

Abstract: The glucocorticoid-induced inhibition that occurs after discontinuation of treatment is the most frequent cause of adrenal insufficiency. There are yet some doubts about the best way of evaluating the hypothalamic-pituitary-adrenal (HPA) axis in those patients. The main objective of this study was to evaluate the utility of basal cortisol in diagnosing adrenal insufficiency. Thirty-five children with acute lymphoid leukemia (ALL) receiving glucocorticoid therapy (median age of 6.9 years) were evaluated. A stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Morning serum cortisol has a high diagnostic accuracy at the extremes of normality (<3 μg/dL or >20.0 μg/dL) [21], whereas intermediate values seem to be less useful, probably due to the lack of adequate sensitivity of non-stimulated measurements for the diagnosis of AI. Prete and Bancos [3] have shown that a morning serum cortisol >350 nmol/L (12.7 μg/dL) rules out secondary AI with high diagnostic efficiency, allowing glucocorticoid therapy to be safely discontinued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morning serum cortisol has a high diagnostic accuracy at the extremes of normality (<3 μg/dL or >20.0 μg/dL) [21], whereas intermediate values seem to be less useful, probably due to the lack of adequate sensitivity of non-stimulated measurements for the diagnosis of AI. Prete and Bancos [3] have shown that a morning serum cortisol >350 nmol/L (12.7 μg/dL) rules out secondary AI with high diagnostic efficiency, allowing glucocorticoid therapy to be safely discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…However, some conflict arises with serum cortisol concentrations between 82.8 and 275.9 nmol/L (3.0–10 μg/dL) [1, 3]. Silva et al [21] found that a baseline serum cortisol level above 234.5 nmol/L (8.5 μg/dL) by the RIA method on day 30 after glucocorticoid withdrawal had a specificity of 86% for HPA recovery. In the present study, we used our local cut-off value of ≥193 nmol/L (7.0 μg/dL) to define adequate morning cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%
“…They have limited sensitivity and specificity for diagnosing SAI and evaluating HPA axis integrity, but they can be performed to identify the baseline level before administrating the stimulus in stimulation tests. 24 However, several measurement tests involve stimulation of the component of the HPA axis and are considered clinically challenging and provide objective data to evaluate the recovery of HPA axis integrity. It should be analysed and interpreted by healthcare professionals due to the difficulty of correlating the biochemical abnormalities with clinical features.…”
Section: Hpa Axis Dynamic Testingmentioning
confidence: 99%
“…Tests not involving stimulation, such as measurement of 32 It is important that cortisol assays (baseline or post-stimulation) be carried out after suspension of corticosteroid therapy, or at least 24 to 48 hours after the last dose, since, with the exception of dexamethasone, the other corticosteroids interfere with the results. 6,39 Measurement of free cortisol in saliva, a noninvasive and easy to obtain method, has not yet been validated for assessing the HPA axis, due to technical difficulties with the tests and due to the need to control variables that interfere with results (for example, nutritional intake, medications).…”
Section: Relapse Of the Underlying Diseasementioning
confidence: 99%